2016
DOI: 10.1016/j.livsci.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of “mono-breed” pork products: Identification of a coat colour gene marker in Cinta Senese pigs useful to this purpose

Abstract: Manuscript as accepted for publication Highlights  Cinta Senese is a local Italian pig breed with a belted coat colour  The value of its meat production chain should be protected from frauds  We analyzed the KIT gene to identify a suitable DNA marker for this purpose  A single nucleotide polymorphism (g.43597545C>T) was almost fixed in Cinta Senese  Probability to correctly assign an unknown meat sample to Cinta Senese was ~1.00.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Thus, full characterization of KIT alleles was beyond the scope of this work. Nevertheless, the KIT g. 43597545C>T (g.41488472 in Sscrofa11.1) SNP was included in the panel, since it had been previously associated to the belted phenotype [ 68 ]. This SNP was proposed as suitable marker for differentiation of Cinta Senese pigs from other non-belted breeds and in agreement our results show a very high frequency of allele T in Cinta Senese (0.98), while most other breeds are fixed or almost fixed for the C allele.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, full characterization of KIT alleles was beyond the scope of this work. Nevertheless, the KIT g. 43597545C>T (g.41488472 in Sscrofa11.1) SNP was included in the panel, since it had been previously associated to the belted phenotype [ 68 ]. This SNP was proposed as suitable marker for differentiation of Cinta Senese pigs from other non-belted breeds and in agreement our results show a very high frequency of allele T in Cinta Senese (0.98), while most other breeds are fixed or almost fixed for the C allele.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, this heterogeneity should be managed to create phenotypically uniform populations that might better match the standard traits defined by their herd books, useful for acquiring a specific identity for these pig genetic resources and making possible the application of DNA‐based systems for the authentication of their products (Fontanesi ; Fontanesi et al . ).…”
Section: Frequencies Of Melanocortin 1 Receptor (Mc1r) and Nuclear Rementioning
confidence: 97%
“…Alves et al analysed porcine mitochondrial DNA and identified SNPs specific to Iberian and Duroc pigs [36]. Another SNP in a nuclear gene encoding v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog ( KIT ) was found to be useful for authentication of meat products obtained from Cinta Senese pigs reared exclusively in Italy [37]. A 96-plex SNP genotyping assay using markers selected from the PorcineSNP60 BeadChip was shown to be a powerful tool for identification of traditional and commercial breeds of domestic pigs from the United Kingdom [38].…”
Section: Discussionmentioning
confidence: 99%